Interactivity, active collaborative learning, and learning performance: The moderating role of perceived fun by using personal response systems. Issue 1 (March 2019) - Chan, Simon C.H.; Wan, C.L. Johnny; Ko, Stephen
Abstract: The aims of this study were to examine the relationships between interactivity, active collaborative learning, and students' learning performance and to determine whether these relationships were moderated by the level of fun students experienced when using personal response systems (PRSs). The participants were 247 undergraduate students studying business at a Hong Kong university. The results indicated that active collaborative learning mediated the relationship between interactivity and students' learning performance. Additionally, high levels of fun experienced as a result of using PRSs strengthened the association between interactivity and students' learning performance.